The Analysis on the writing styles of O. Henry - Barlikbayeva Gulmira Kaljanovna (Zien Journals, 2024)
Henry was a well-known American writer in the world literature history. His writing is vivid and he is good at using irony, paronomasia, metaphor, metonymy and exaggeration to make the story full of fun. He is a master of surprising endings, and he usually design story plots dramatically, and makes some unexpected changes at the end, which is quite out of readers’ expectations. Another writing style of his novel is tearful smile, and it is the combination of comedy and tragedy. In a word, O. Henry’s typical writing styles can be concluded as follows: humorous language, surprising endings, and tearful smile
Keywords: Henry; Writing Styles; Humorous Language